2006
DOI: 10.1002/ajim.20313
|View full text |Cite
|
Sign up to set email alerts
|

Parental exposure to lead and small for gestational age births

Abstract: Additional evidence of the effects of lead on adverse birth outcomes, especially for SGA births is reported. Maternal exposure to lead plays a more important role in the adverse effect on birth outcome than does paternal exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The effects of B-Pb on preterm delivery (or length of gestation) and LBW (or small-for-gestational-age) are similarly divided in the literature, with some authors reporting no effect on one or both of the variables,7,8,46,47 and others reporting linear associations,16,18 or a doubling37 or even trebling10 of risk for B-Pb > 10  μ g/dl (see Table S2). In line with these findings, but using a lower cut-off level of 5  μ g/dl, we found that the risk of preterm delivery in women with levels ≥ 5  μ g/dl was twice that in women with levels < 5  μ g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of B-Pb on preterm delivery (or length of gestation) and LBW (or small-for-gestational-age) are similarly divided in the literature, with some authors reporting no effect on one or both of the variables,7,8,46,47 and others reporting linear associations,16,18 or a doubling37 or even trebling10 of risk for B-Pb > 10  μ g/dl (see Table S2). In line with these findings, but using a lower cut-off level of 5  μ g/dl, we found that the risk of preterm delivery in women with levels ≥ 5  μ g/dl was twice that in women with levels < 5  μ g/dl.…”
Section: Discussionmentioning
confidence: 99%
“…26 Maternal lead exposure during pregnancy was reported to negatively affect gestational length and to increase the risk of preterm and small-for-gestational age infants. 1,11,12,14,25,27 However, in these studies, the lead levels in maternal blood were .5 mg/dL, thus the effects of the very low levels currently observed in developed countries are still to be thoroughly evaluated. In addition, environmental constraints on fetal growth may not only affect birth outcomes, but also have lasting effects on postnatal growth.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although the sensitive period remains undetermined, prenatal exposure to lead is of particular concern because lead is known to cross the placenta and cause adverse birth outcomes, such as preterm birth, low birth weight, and small for gestational age. 1,[10][11][12][13][14][15] Schell et al 12 found that maternal blood lead levels of $3 mg/dL during the second trimester were associated with reduced head circumference at 6 and 12 months, but had no significant effects at ,3 mg/dL. Afeiche et al, 16 in a follow-up study of attained child weight, found that prenatal maternal bone lead was associated with lower weight over time among girls up to 5 years of age.…”
mentioning
confidence: 99%
“…In general, the literature regarding metal exposure and fetal growth outcomes is inconsistent. Some studies report an association (Rahman et al, 2009;Llanos and Ronco, 2009;Bellinger et al, 1991;Chen et al, 2006;Foldspang and Hansen, 1990;Hopenhayn et al, 2003;Kippler et al, 2011;Lee et al, 2010;Lin et al, 2011;Nishijo et al, 2004;Odland et al, 1999;Osman et al, 2000;Ramón et al, 2009;Shirai et al, 2010;Tian et al, 2009;Xie et al, 2013;Yang et al, 2003;Zhu et al, 2010) while others report no association (Odland et al, 1999;Osman et al, 2000;Ding et al, 2013;Daniels et al, 2007;Galicia-García et al, 1997;Jones et al, 2010;Sowers et al, 2002;Menai et al, 2012;Loiacono et al, 1992;Lucas et al, 2004). Few studies have examined low-level exposure as currently experienced in most developed countries such as Canada, thus any resultant health effects are relatively unknown.…”
mentioning
confidence: 87%